Using a Multilevel Modeling Approach to Quantify the Side Effects of Cranial Electrotherapy Stimulation on Motor and Cognitive Tasks in Healthy Young Adults - Sansevere, Kayla. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Psychology.; Advisor: Nathan Ward.; Committee: Tad Brunyé, and Sara Johnson.; Keyword: Experimental psychology.